VD_FINDINFO Arrêt / 2016 / 1019 vom 31. Oktober 2016 - VD Tribunal cantonal (2016)
RENTE D'INVALIDITÉ, AA, LOI FÉDÉRALE SUR L'ASSURANCE-ACCIDENTS, ÉVALUATION DE L'INVALIDITÉ | 29 al. 2 Cst., 18 LAA, 16 LPGA, 17 al. 1 LPGA